Scalable and selective electrochemical benzylic C-H fluoroetherfication to fluorinated ethers - Kong, yanyan; Wang, chao; Xu, xuemei; Yang, zekun (Synthesis)
lectrochemical dehydrogenative cross-coupling reaction has become a powerful strategy to construct C-O bond. However, electrochemically induced benzylic C-H fluoroetherfication still remains challenge due to the limitation of prefunctionalization, using metal-catalysts and chemical oxidants, multi-steps and narrow substrate scope. Herein, we present a green and efficient approach to synthesize diverse fluorinated ethers with ethylbenzenes and fluoroalcohols as substrates. This protocol exhibited good scalability. Mechanistic insights suggested that the radical might be involved in this reaction.